THE RELATIONSHIP BETWEEN PREMENSTRUAL SYNDROME WITH INSOMNIA IN MEDICAL STUDENTS AT UNIVERSITAS NUSA CENDANA - Permatasari, Gusti Ayu Angeliene; Lidia, Kartini; Handoyo, Nicholas Edwin; Kareri, Dyah Gita Rambu (Indonesian Journal for Health Sciences, 2024)
Menstrual disorders, one of which is Premenstrual Syndrome (PMS), are still Indonesia's most common health problem. PMS symptoms appear during the luteal phase that occurs 7-14 days before menstruation. During premenstrual syndrome, there will be a hormonal imbalance that can cause insomnia. Insomnia is difficulty sleeping, difficulty maintaining sleep (frequent awakenings at night), or waking up too early accompanied by drowsiness during the day, as well as poor sleep quality that occurs at least three times a week for a month. Insomnia can interfere academic performance of students. This study aims to analyze the relationship between PMS and insomnia in Medical students of Universitas Nusa Cendana. The research design used cross-sectional, and it was attended by 137 medical students of Universitas Nusa Cendana who were selected with total sampling. Data collection online used The Shortened Premenstrual Assessment Form (SPAF) and the Pittsburgh Sleep Symptom Questionnaire-Insomnia (PSSQ_I). The data analysis used is the Chi-Square test. There was a significant relationship between PMS and insomnia in medical students of Universitas Nusa Cendana, with a p-value of 0.000.